2018
DOI: 10.3748/wjg.v24.i22.2381
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of hypoxia-inducible factor-1 alpha and prolyl 4-hydroxylase beta polypeptide overexpression in gastric cancer

Abstract: AIMTo investigate the relationship between hypoxia-inducible factor-1α (HIF-1α), prolyl 4-hydroxylase beta (P4HB) expression, and clinicopathologic parameters, as well as the prognostic value of these genes for patients with gastric cancer (GC).METHODSHypoxia is a critical factor that shapes the GC microenvironment. In previous reports, we have demonstrated that P4HB is a potential target of HIF-1α. In the present study, gene expression profiling interactive analysis (GEPIA) was used to analyze the relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 41 publications
(43 reference statements)
1
37
0
2
Order By: Relevance
“…Although traditional treatment strategies have improved, the 5-year survival rate is still low. 15 Therefore, it is critical that GC is diagnosed early, and finding a suitable plasma molecular biomarker may be an effective method to achieve this goal. Several studies have demonstrated the feasibility of using circulating lncRNAs as biomarkers for tumor diagnosis; however, numerous preanalytical and analytical aspects, such as sample choice, extraction method, and donor-related factors, may affect the accuracy of circulating lncRNA determination.…”
Section: Discussionmentioning
confidence: 99%
“…Although traditional treatment strategies have improved, the 5-year survival rate is still low. 15 Therefore, it is critical that GC is diagnosed early, and finding a suitable plasma molecular biomarker may be an effective method to achieve this goal. Several studies have demonstrated the feasibility of using circulating lncRNAs as biomarkers for tumor diagnosis; however, numerous preanalytical and analytical aspects, such as sample choice, extraction method, and donor-related factors, may affect the accuracy of circulating lncRNA determination.…”
Section: Discussionmentioning
confidence: 99%
“…The steps of immunohistochemistry were performed as formerly described. 10 The ultimate immunoreactivity scores (IRS) were calculated consistent with the scores of the ratio of positive dyed cells, as previously described. 10 …”
Section: Methodsmentioning
confidence: 99%
“…In experimental models, the activation of this pathway has been shown to promote the progression of gastric cancer (53). HIF-1 can up-regulate EMT-related transcription factors and is closely related to the prognosis of gastric cancer (54). Those results led us to speculate on the key role of DLEU2 in tumor hypoxia.…”
Section: Discussionmentioning
confidence: 93%